Present and Potential Future Distributions of Asian Horseshoe Crabs Determine Areas for Conservation - Vestbo, Stine; Obst, Matthias; Quevedo Fernandez, Francisco J.; Intanai, Itsara; Funch, Peter (Frontiers in Marine Science, 2018)
Conservation of horseshoe crabs has recently received increasing attention as several populations are in decline. However, scarce information on their distributions in Southeast Asia is impairing conservation efforts. In this study, we sought to improve our understanding of the geographical range and distinct populations of the three Asian horseshoe crabs species in order to identify optimal conservation areas. We mapped the geographic range of Carcinoscorpius rotundicauda, Tachypleus gigas, and T. tridentatus using recent data from field work, literature, Global Biodiversity Information Facility (GBIF), and unpublished data from our scientific network. The data were correlated with 23 different environmental variables of potential ecological importance for horseshoe crabs using the openModeller webservices, including new tidal variables. Ecological niche models were generated using two algorithms, Maximum Entropy and support vector machine, for the three species under present conditions, and projected into a climate change scenario of 2050. The niches of the Asian horseshoe crabs were mostly determined by tidal regime, chlorophyll A concentrations, depth, distance to land, and sea surface temperature. According to our predictions, horseshoe crabs in Southeast Asia are not expected to experience any severe change in extent and distribution of suitable habitat in the future. In order to conserve Asian horseshoe crabs, we suggest establishing Marine Protected Areas at locations where distinct populations and several species occur, such as northern Vietnam, China, Borneo, and southern Japan.